Cuttlefish ink-based N and S co-doped carbon quantum dots as a fluorescent sensor for highly sensitive and selective para-nitrophenol detection. Issue 44 (3rd November 2021) - Huang, Xiaotong; Yang, Chunli; Chen, Yingxin; Zhu, Zebin; Zhou, Lihua
Abstract : Cuttlefish ink-based N and S co-doped carbon quantum dots exhibit two optimal emissions at the emission wavelengths of 385 and 465 nm, achieving highly sensitive and selective detection of PNP. The detection mechanisms were explored as IFE and PET. Abstract : Para -nitrophenol (PNP) is an important raw material for organic synthesis and its extensive use has produced a series of environmental problems. Here, we develop a highly sensitive and selective fluorescent detection method for PNP with cuttlefish ink-based carbon quantum dots (CQDs). The cuttlefish ink, which is rich in eumelanin, is utilized as the only precursor to synthesize the CQDs via a one-step hydrothermal method. The resultant CQDs were co-doped with nitrogen and sulfur and exhibited excellent fluorescence properties. Two optimal emissions can be observed at the excitation/emission wavelengths of 320/385 nm and 390/465 nm, respectively. In the presence of PNP, the two emissions are remarkably quenched. PNP can be measured in the linear detection concentration range of 1.25–50 μM (Em = 385 nm and R 2 = 0.9884) or 1.25–27.5 μM (Em = 465 nm and R 2 = 0.9818) with a detection limit of 0.05 μM. Significantly, it is found that a much wider linear detection range of 0.05–125 μM with a lower detection limit of 0.039 μM (3 σ / k ) can be achieved when log( I 385 nm + I 465 nm ) was utilized to quantify PNP. The investigations of the sensing mechanism suggested that the inner filter effect and photoinduced electron transfer of PNP and N, S-CQDs leads to fluorescence quenching. The sensing method is successfully applied for PNP detection in real water samples with satisfactory recoveries (91.18–103.14%). A new sustainable waste-prevention strategy of cuttlefish ink and a feasible alternative to PNP detection methods is provided in this article.